2016
DOI: 10.1161/strokeaha.116.014998
|View full text |Cite
|
Sign up to set email alerts
|

Association of Retinopathy and Retinal Microvascular Abnormalities With Stroke and Cerebrovascular Disease

Abstract: Abnormalities of the retinal microvasculature are independently associated with stroke, cerebral infarcts, and white matter lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 13 publications
(11 reference statements)
2
38
1
Order By: Relevance
“…As the retinal microvasculature shares embryologic, anatomic, and regulatory characteristics with that of the cerebral circulation (35,36), one would expect that retinal changes parallel those in the cerebral vasculature, with the association of SDR with stroke being particularly strong. Nevertheless, such an association has been seen in individuals with type 2 diabetes (37,38), in the general population (3,5), and even in individuals with T1D, as previously shown by us (12). One possible explanation for this discrepancy could again be that the patients analyzed in the current study had a substantially longer diabetes duration, reflecting a changing picture of vascular risk factors at different stages of diabetes duration.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…As the retinal microvasculature shares embryologic, anatomic, and regulatory characteristics with that of the cerebral circulation (35,36), one would expect that retinal changes parallel those in the cerebral vasculature, with the association of SDR with stroke being particularly strong. Nevertheless, such an association has been seen in individuals with type 2 diabetes (37,38), in the general population (3,5), and even in individuals with T1D, as previously shown by us (12). One possible explanation for this discrepancy could again be that the patients analyzed in the current study had a substantially longer diabetes duration, reflecting a changing picture of vascular risk factors at different stages of diabetes duration.…”
Section: Discussionsupporting
confidence: 56%
“…Curiously, however, in our previous study, there was no link found between the lacunar stoke proportion and SDR, even though lacunar stroke is regarded as a microvascular cerebral disease (39). The underlying explanation may be that rather than the typical signs of SDR, more subtle changes in the retinal vascular architecture, such as changes in the arterio-venular ratio and microvascular branching are associated with cerebral disease, highlighting the role of more detailed studies of retinal microvasculature for CVD risk determination (3,5) in individuals with T1D.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…14,15 Retinopathy and changes in retinal vessel caliber are associated with renal and cardiovascular disease, even in low risk individuals without diabetes or kidney disease at baseline. 1629 We previously demonstrated in individuals with stage 2–4 CKD enrolled in the Chronic Renal Insufficiency Cohort (CRIC) Study that higher serum phosphate was significantly associated with more severe retinopathy and greater retinal venular diameter, independent of classic risk factors for retinal vascular disease, such as hypertension and diabetes. 14 However, there are no prospective studies investigating if a higher serum phosphate level is a risk factor for the development or progression of retinopathy or changes in retinal vessel caliber in individuals with or without CKD.…”
Section: Introductionmentioning
confidence: 99%
“…22 The retina shares common embryological and physiological features with the central nervous system, and retinal vascular photography provides a cheaper, quicker and non-invasive way of indirectly measuring SVD. In cross-sectional studies in the general HIV-negative population, retinal vascular abnormalities (measured quantitatively by vessel diameters or qualitatively by as retinopathy) have been found to be independently associated with the extent of white matter hyperintensities 23,24 and the presence of dementia in people with hypertension. 25 In cohorts, similar markers are independently associated with progression of cerebrovascular SVD 26 and ventricular enlargement.…”
Section: Introductionmentioning
confidence: 99%